Atmospheric abundances of black carbon aerosols and their radiative impact over an urban and a rural site in SW India. (January 2016) - Raju, M.P.; Safai, P.D.; Vijayakumar, K.; Devara, P.C.S.; Naidu, C.V.; Rao, P.S.P.; Pandithurai, G.
Abstract: Observations on black carbon (BC) aerosols over an urban site (Pune) and a rural, high altitude site (Sinhagad) during summer and winter seasons over the period of 2009–2013 are reported. Apart from the temporal variation of BC over both the sites, its mass fraction to total suspended particulates (TSP) is studied. Finally, using the chemical composition of TSP and BC in the OPAC model, season-wise optical properties of aerosols are obtained which are further used in the SBDART model to derive the aerosol radiative forcing (ARF) at surface and top of the atmosphere and thereby the atmospheric forcing and heating rates in each season over both the sites. BC mass concentration and its mass fraction to TSP (Mf BC) were higher at Pune than at Sinhagad, indicating impact of more anthropogenic sources. At both the sites winter season witnessed higher BC concentrations than summer as well as higher Mf BC which is due to the prevailing favorable meteorological conditions in winter. Diurnal variation of BC showed different patterns at Pune and Sinhagad in terms of strength and occurrence of high and low values that could be attributed to varying local boundary layer conditions and source activities at both the sites. Negative ARF indicated cooling at top of the atmosphere and at surface leading to warming of the atmosphere at both the sites. However, surface cooling and atmospheric warming was more dominant at Pune leading to higher atmospheric heating rates, underlining the impact of absorbing BC aerosols which were about three times more at Pune than Sinhagad. Highlights: Long term seasonal BC climatology at two environmentally different sites in SW India. Three times more BC at Pune (urban site) than at Sinhagad (rural site). BC enhancement in winter in terms of concentration and mass fraction to TSP. Significant cooling at SUF and warming at ATM leading to high heating rates.